Impact of alcoholic extract from sea cucumber (Holothuria parva) on letrozole–induced polycystic ovary syndrome in adult female rats - Samaneh Askari; Mohammad Reza Jafarzadeh Shirazi; Masoumeh Ahmadi; Arezoo Khoradmehr; Nadiar M. Mussin; Asset A. Kaliyev; Farzad Mohammad Rezazadeh; Mohammad Dadpasand Taromsari; Ali Bustani; Nader Tanideh; Kulyash R. Zhilisbayeva; Amin Tamadon (Asian Pacific Journal of Reproduction)
Objective: To explore the potential therapeutic impact of an alcoholic extract derived from the sea cucumber (Holothuria parva) on letrozole-induced polycystic ovary syndrome (PCOS) in adult female Sprague-Dawley rats. Methods: Sixteen female rats, aged 8 to 10 weeks, with a mean weight of (200±20) g, were randomly assigned to four groups: the control, PCOS, and two treatment groups receiving sea cucumber extract and metformin, respectively. PCOS was induced by administering letrozole at a dose of 1 mg/kg to initiate the treatment period at 60 days of age. The study spanned four weeks, during which ovarian and uterine tissues were collected for histological examination, and blood samples were collected for hormonal levels. Results: Significant decreases in luteinizing hormone/follicle stimulating hormone (LH/FSH) and testosterone and increases progesterone levels among groups treated with sea cucumber extract were observed. While no significant differences were observed in follicle-stimulating hormone (FSH) and testosterone levels, the distinctive variations in key hormones suggested a potential role for sea cucumber alcoholic extract in ameliorating PCOS symptoms. Conclusions: This research highlights the moderate efficacy of sea cucumber extract as a therapeutic intervention for PCOS, providing a novel perspective in the search for effective remedies. The observed hormonal alterations, particularly in LH, estradiol, and progesterone, underscore the need for further exploration into the underlying mechanisms and for optimizing the application of sea cucumber extract in PCOS management.